2020
DOI: 10.3390/v12050516
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analyses of Human Sapoviruses Detected over a 40-Year Period Reveal Disparate Patterns of Evolution among Genotypes and Genome Regions

Abstract: Human sapovirus is a causative agent of acute gastroenteritis in all age groups. The use of full-length viral genomes has proven beneficial to investigate evolutionary dynamics and transmission chains. In this study, we developed a full-length genome sequencing platform for human sapovirus and sequenced the oldest available strains (collected in the 1970s) to analyse diversification of sapoviruses. Sequence analyses from five major genotypes (GI.1, GI.2, GII.1, GII.3, and GIV.1) showed limited intra-genotypic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 73 publications
2
11
0
Order By: Relevance
“…Similar observations were made previously in diarrheic cases in Southeast Asia ( 55 ), even though subgroup B and C adenoviruses are commonly associated with respiratory infections ( 59 ). Few members of the Caliciviridae (including the globally circulating SV GI.2) were detected at low prevalence in our study, which was rather unexpected, as they are frequently reported in gastroenteritis ( 15 , 60 ).…”
Section: Discussionsupporting
confidence: 41%
“…Similar observations were made previously in diarrheic cases in Southeast Asia ( 55 ), even though subgroup B and C adenoviruses are commonly associated with respiratory infections ( 59 ). Few members of the Caliciviridae (including the globally circulating SV GI.2) were detected at low prevalence in our study, which was rather unexpected, as they are frequently reported in gastroenteritis ( 15 , 60 ).…”
Section: Discussionsupporting
confidence: 41%
“…To trace the distribution of sapovirus genotypes in different settings and geographical areas is relevant, as this information is epidemiologically useful to design and develop broadly protective sapovirus vaccines [ 1 ]. Even though several sapovirus recombinant strains of both intragenogroup and intergenogroup recombinations have been reported [ 18 , 25 , 44 ], sequence analyses from five major genotypes (GI.1, GI.2, GII.1, GII.3, and GIV.1) have shown, contrary to noroviruses, limited intra-genotypic diversification for over 40 years [ 45 ]. The relationship between sapovirus genotypes and serotypes is still unknown and more studies are needed to clarify this question, but this observation gives hope to the future development of sapovirus vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…The genome sequences of some GIII strains shared only 85.8% nt identities. Both intra‐ and inter‐genogroup recombinant strains have been reported for porcine SaV (Kuroda et al., 2017; Li et al., 2017; Wang et al., 2020; Wang et al., 2005) as well as human SaV (Dey et al., 2018; Kumthip et al., 2020; Lasure & Gopalkrishna, 2017; Liu et al., 2015; Tohma et al., 2020). However, most of the recombinant studies were performed with reference strains and few field strains have been investigated for recombination.…”
Section: Discussionmentioning
confidence: 99%